Application of Learning Models of Concept Attainment and Problem Based Learning Against High School Students' Creative Thinking Ability on Redox Material - Lisa N. M. Sakaria; Kasmudin Mustapa; Anang Wahid M. Diah (Jurnal Akademika Kimia, 2021)
Creative thinking is thinking to determine the new relationships between things, such as finding new solutions to a problem, finding new systems, and finding new artistic forms. This study aimed to analyze students' creative thinking ability by applying concept attainment and problem-based learning models in the redox material of class X SMA Negeri 9 Palu. This type of research was pre-experimental with the static group pre-test post-test design. This study used 2 classes, namely class X MIA 1 as experimental class 1 (n = 22) and class X MIA 2 as experimental class 2 (n = 22). Data analysis of students’ creative thinking was performed using the test given after learning (post-test). The results of this study indicated that the percentage value of the average creative thinking of the experimental class 1 students was 74.5% with the high category and the achievement of aspects of creative thinking of students with the percentage from highest to lowest in the originality aspect were 76.7%, flexibility aspect was 74.1%, and the fluency aspect was 72.7%. While the average percentage of experimental class 2 was 76.6% with the high category and the achievement of aspects of creative thinking of students with the highest to lowest percentage of the fluency aspect was 84.5%, the originality aspect was 75.1%, and the flexibility aspect was 70.2%. The results of this study can be concluded that the application of the Concept Attainment and Problem Based Learning models were very good in creative thinking skills of students class in SMA Negeri 9 Palu on Redox material.